Copper Removal from Aqueous Solutions Using Macro Alga (Ulva lactuca): Equilibrium and Kinetic Studies - Oktem, Y.A. (Asian Journal of Chemistry, 2013)
The removal mechanism of Cu2+ from aqueous solutions using a dried and untreated macro algae species (Ulva lactuca) as the adsorbent was investigated. The equilibrium data obtained from the adsorption of the metal ions was in good accordance with the Langmuir isotherm and the maximum adsorption capacity (Qm) was calculated as 38 mg/g. Lagergren pseudo-first order and pseudo-second order reaction rate equations were used to calculate adsorption rate of copper. Best model of copper adsorption rate was as determined pseudo-second order rate model.